CD47 deficiency ameliorates autoimmune nephritis in Faslpr mice by suppressing IgG autoantibody production. Issue 3 (14th July 2015) - Shi, Lei; Bian, Zhen; Chen, Celia XJ; Guo, Ya‐Nan; Lv, Zhiyuan; Zeng, Caihong; Liu, Zhihong; Zen, Ke; Liu, Yuan
Abstract: CD47, a self‐recognition marker, plays an important role in both innate and adaptive immune responses. To explore the potential role of CD47 in activation of autoreactive T and B cells and the production of autoantibodies in autoimmune disease, especially systemic lupus erythematosus (SLE), we have generated CD47 knockout Fas lpr (CD47 −/− − Fas lpr ) mice and examined histopathological changes in the kidneys, cumulative survival rates, proteinuria, extent of splenomegaly and autoantibodies, serum chemistry and immunological parameters. In comparison with Fas lpr mice, CD47 −/− − Fas lpr mice exhibit a prolonged lifespan and delayed autoimmune nephritis, including glomerular cell proliferation, basement membrane thickening, acute tubular atrophy and vacuolization. CD47 −/− − Fas lpr mice have lower levels of proteinuria, associated with reduced deposition of complement C3 and C1q, and IgG but not IgM in the glomeruli, compared to age‐matched Fas lpr mice. Serum levels of antinuclear antibodies and anti‐double‐stranded DNA antibodies are significantly lower in CD47 −/− − Fas lpr than in Fas lpr mice. CD47 −/− – Fas lpr mice also display less pronounced splenomegaly than Fas lpr mice. The mechanistic studies further suggest that CD47 deficiency impairs the antigenic challenge‐induced production of IgG but not IgM, and that this effect is associated with reduction of T follicular cells and impairment of germinal centre development in lymphoid tissues. In conclusion, our results demonstrate that CD47 deficiency ameliorates lupus nephritis in Fas lpr mice via suppression of IgG autoantibody production. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.